Pregnancy under control. Modern methods of determining ovulation - I N Korotkykh; O S Kryshtopina (IP Berlin A.V., 2015)
The definition of ovulation moment, during which the probability of conception is maximal, can be considered as the basis for planning pregnancy. The following article deals with the accessibility and effectiveness of methods for determining ovulation tests; the evaluation of their benefits is based on immuno-chromatographic determination of the peak concentrations of luteinizing hormone.